PENINGKATAN PEMAHAMAN MATEMATIS DAN DISPOSISI MATEMATIS DENGAN STRATEGI MATHEMATICAL HABITS OF MIND - Zuraida IM; Rahmah Johar; Hajidin . (Universitas Syiah Kuala, 2013)
This research to aim to study differenced understanding of mathematics and disposition mathematics between student can learning using strategy of MHM and student can learning of conventional. This research as study of experiment quasi with design planning Pre-tes post-test control group design. Subject of population is all student class XI Senior High School 2 Sigli with sampel two class (experiment and control class) to pass technical random sampling of seven class parallel have its. Collecting data with using instrument is test. Test include test understanding of mathematics, scale of disposition, and LKK understanding of mathematics. To see differenced understanding mathematics student between strategy of MHM with conventional group using t-test in significancy 0,05 after fulfilled condition. Base on data of test statistic after that using programme SPSS 17 for Windows and Microsoft Excell 2007 to interpretation understanding and disposition student for learning with strategy MHM. Using strategy MHM in learning really can impact understanding and disposition mathematics student is better, in quality can differenced significancy between student learning using strategy of MHM and approximation conventional.